(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Words are categorized based on their parts of speech, which serve essential functions in sentence structure and meaning. The French language includes eight fundamental parts of speech: nouns (un nom or un substantif), verbs (un verbe), adjectives (un adjectif), adverbs (un adverbe), pronouns (un pronom), articles (un article), prepositions (une préposition), conjunctions (une conjonction). This study examines the classification of word groups in the French language.